Study Protocol on Intentional Distortion in Personality Assessment: Relationship with Test Format, Culture, and Cognitive Ability - Van Geert, Eline; Orhon, Altan; Cioca, Iulia A.; Mamede, Rui; Golušin, Slobodan; Hubená, Barbora; Morillo, Daniel (Frontiers in Psychology, 2016)
Self-report personality questionnaires, traditionally offered in a graded-scale format, are widely used in high-stakes contexts such as job selection. However, job applicants may intentionally distort their answers when filling in these questionnaires, undermining the validity of the test results. Forced-choice questionnaires are allegedly more resistant to intentional distortion compared to graded-scale questionnaires, but they generate ipsative data. Ipsativity violates the assumptions of classical test theory, distorting the reliability and construct validity of the scales, and producing interdependencies among the scores. This limitation is overcome in the current study by using the recently developed Thurstonian item response theory model. As online testing in job selection contexts is increasing, the focus will be on the impact of intentional distortion on personality questionnaire data collected online. The present study intends to examine the effect of three different variables on intentional distortion: (a) test format (graded-scale versus forced-choice); (b) culture, as data will be collected in three countries differing in their attitudes toward intentional distortion (the United Kingdom, Serbia, and Turkey); and (c) cognitive ability, as a possible predictor of the ability to choose the more desirable responses. Furthermore, we aim to integrate the findings using a comprehensive model of intentional distortion. In the discussion, three main aspects are considered: (a) the limitations of the manipulation, theoretical approach, and analyses employed; (b) practical implications for job selection and for personality assessment in a broader sense; and (c) suggestions for further research.